Provisional checklist of genera of the Pieridae (Lepidoptera: Papilionoidea) - Braby, Michael F. (Zootaxa, 2005)
A provisional list of lower taxa (genera, subgenera) for the butterfly family Pieridae is provided based on review of the literature. A total of 98 taxa (83 genera, 15 subgenera) is recognised. Most of the genera appear in relatively good order but there is considerable doubt concerning the monophyly of Eurema sensu lato, Eurema sensu stricto, Catasticta sensu lato and Appias sensu lato. Systematic revision of Eurema sensu lato, Phoebis sensu lato, Hesperocharis sensu lato and Appias sensu lato is also required to determine the status or taxonomic rank (i.e. genera or subgenera) of taxa currently or previously included in these genera in the broad sense. The status of subgenera currently assigned to Colias sensu stricto appears doubtful. It is recommended that future systematic studies on lower classification focus on recognition of species-groups rather than subgenera within monophyletic genera.